2013
DOI: 10.3346/jkms.2013.28.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Improved Therapeutic Effect against Leukemia by a Combination of the Histone Methyltransferase Inhibitor Chaetocin and the Histone Deacetylase Inhibitor Trichostatin A

Abstract: SUV39H1 is a histone 3 lysine 9 (H3K9)-specific methyltransferase that is important for heterochromatin formation and the regulation of gene expression. Chaetocin specifically inhibits SUV39H1, resulted in H3K9 methylation reduction as well as reactivation of silenced genes in cancer cells. Histone deacetylase (HDAC) inhibitors inhibit deacetylases and accumulate high levels of acetylation lead to cell cycle arrest and apoptosis. In this study, we demonstrated that treatment with chaetocin enhanced apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In this study, chaetocin remarkably suppressed the tumorigenicity of HCC cells in culture and in a xenograft transplantation model. Chaetocin reduced H3K9me3 levels as well as SUV39H1 levels in a dose‐dependent manner in HCC cells, which was also reported for human leukemic cells …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, chaetocin remarkably suppressed the tumorigenicity of HCC cells in culture and in a xenograft transplantation model. Chaetocin reduced H3K9me3 levels as well as SUV39H1 levels in a dose‐dependent manner in HCC cells, which was also reported for human leukemic cells …”
Section: Discussionsupporting
confidence: 77%
“…Chaetocin reduced H3K9me3 levels as well as SUV39H1 levels in a dose-dependent manner in HCC cells, which was also reported for human leukemic cells. 31 Although the pharmacological mechanism of chaetocin has not yet been completely elucidated, chaetocin might have a direct effect to reduce the SUV39H1 protein. Considering that chaetocin was found to modulate the expression of various cancer-related genes, 32,33 another possibility is that altered expressions of these genes might cause a secondary downregulation of SUV39H1.…”
Section: Discussionmentioning
confidence: 99%
“…Chaetocin is an inhibitor that inhibits methyltransferase Suv39h1 and reduces H3K9 repressive markers (78). Chaetocin treatment in human leukemia cells inhibits H3K9 methylation and reactivates the expression of E-cadherin and tumor suppressor p15 (79, 80). Further studies are needed to investigate the effect of H3K9-specific methyltransferase inhibitors on gene expression and the therapeutic response of cancer cells during hypoxia.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…Two recent studies demonstrated that chaetocin in addition to inhibit SUV39H1 enzymatic activity also reduced protein level of this methyltransferase. 28 , 29 One of the studies revealed that chaetocin at high concentration acts as a heat shock protein 90 (HSP90) inhibitor and induces degradation of a number of HSP90 client proteins including SUV39H1. 29 These results make the story of chaetocin more complex and suggest that anti-cancer action of chaetocin is time, dose and cell-context dependent.…”
Section: Discussionmentioning
confidence: 99%